SOME APPROACH TO HISTORY ISSUES OF THE WORLD AND VIETNAM - Pham Ngoc Tram (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The context of globalization and the industrial revolution 4.0 has had a strong impact on all fields of science and history that are not outside the above rules. In recent years, the history of the world and Vietnam has changed in their approach to historical problems. Towards the above problem, the article mentions a number of research approaches and theory applied by historians of the world today; New approach of Vietnamese history. On the basis of dialectical materialism, Vietnamese historians step by step change their approach and move towards the transdisciplinary and interdisciplinary application in solving historical problems.